The Intergenerational Transmission of Inequality for Education and Earnings - Beenstock, Michael (Journal of Income Distribution®, 2009)
Inequality is transmitted intergenerationally because the outcomes of parents and their children are correlated. The correlation may be due to inherited, economic, and/or contextual factors. A structural model is proposed in which parents affect their children directly through their own schooling and earnings and indirectly through their own inherited ability. By taking account of inherited ability, the causal effect on outcome of parental schooling and earnings upon the schooling and earnings of their children is identified. A generated regressor methodology is used to estimate the ability to learn and earn of Israeli parents. It is shown that the schooling and earnings of children are affected by these generated regressors. Further, although the causal effects are small, it is shown that parents’ income and schooling matter for their children’s schooling and earnings. Both nature and nurture are reflected in the intergenerational correlation for schooling and earnings, but nature and contextual variables turn out to matter more than nurture.